Some approaches to assessing the quality of atmospheric air in an industrial city using the calculation of the pollutants concentration by gross emissions - Misiuchenka, Viktoryia M.; Pinchuk, Anastasya V.; Rovenskaya, Irina A. (Journal of the Belarusian State University. Ecology, 2021)
The article proposes a method for assessing the quality of atmospheric air based on the gross emissions of individual pollutants. The method allows to assess the air quality without carrying out instrumental measurements. The effectiveness of the introduction of air protection measures is also analyzed on the example of an industrial center of the Republic of Belarus. The general dynamics of pollutant emissions for the industrial city are examined and the results of statistical data on the costs of measures for the atmospheric air protection are presented. It has been established that an increase in capital and operating costs does not affect the amount of substances emitted into the atmospheric air.